(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This presentation is about the relationship between university intangible heritage, university extension, teaching and communication research based on the investigative / creative experience of a study culmination exercise that had the University Theater of Havana as its central axis. It reflects on research for communicative production at the methodological level, emphasizing the creativity-scientific rigor binomial. In a second moment, from a patrimonial and communicative perspective, the projection in the public sphere and of the values of the University of Havana is collected, beyond its institutional conception, to see it as a community with collective values and identities that have perpetuated traditions that become intangible heritage. Starting from this base, the interrelation between the university extension and the academic campus is outlined, which is evidenced in the trajectory documented by the thesis of the University Theater of Havana, which takes into account a history of uninterrupted work —with its ups and downs— in the constitution of a movement of amateur artists in the Cuban university student body. Finally, by way of conclusions, the challenges and debates of the extension movement in an increasingly complex, interconnected and dynamic community such as the University of Havana are related in the present work.